Immiscible Displacement of Non-Newtonian Fluids in Communicating Stratified Reservoirs - El-Khatib, Noaman A.F. (Society of Petroleum Engineers, 2006)
The displacement of non-Newtonian power-law fluids in communicating stratified reservoirs with a log normal permeability distribution is studied. Equations are derived for the fractional oil recovery, water cut, and injectivity ratio at times of breakthrough in the successive layers of the reservoir. Many of the resulting equations are implicit in nature and an iterative solution procedure is used. Expressions are also derived for the pseudo relative permeabilities as function of the average saturation.The performance is compared with that for the Newtonian fluids. The effect of the different parameters on the performance is investigated. These parameters included the apparent mobilityity ratio, the power-law flow behavior indexes, the Dykstra-Parsons variation coefficient, and the flow rate. Constant injection rate and constant total pressure drop cases are studied.